Myocardial stiffness assessed by natural shear wave elastography is related to pressure-volume loop derived parameters. (14th October 2021) - Bezy, S; Caenen, A; Duchenne, J; Orlowska, M; Amoni, M; Keijzer, L B H; Vos, R; D'hooge, J; Voigt, J U
Abstract: Background: Several cardiovascular disorders are accompanied by a stiffening of the myocardium and may result in diastolic heart failure. The non-invasive assessment of myocardial stiffness could therefore improve the understanding of the pathophysiology and guide treatment. Shear wave elastography (SWE) is a recent technique with tremendous potential for evaluating myocardial stiffness in a non-invasive way. Using high frame rate echocardiography, the propagation speed of shear waves is evaluated, which is directly related to the stiffness of the myocardium. These waves are induced by for instance mitral valve closure (MVC) and propagate throughout the cardiac muscle. However, validation of SWE against an invasive gold standard method is lacking. Purpose: The aim of this study was to compare echocardiographic shear wave elastography against invasive pressure-volume loops, a gold standard reference method for assessing chamber stiffness. Methods: In 15 pigs (31.2±4.1 kg) stiffness of the myocardium was acutely changed by inducing ischemia/reperfusion (I/R) injury. For this, the proximal LAD was balloon occluded for 90 minutes with subsequent reperfusion for 40 minutes. Conventional and high frame rate echocardiographic images were acquired simultaneously with pressure-volume loops during baseline conditions and after the induction of the I/R injury. Preload was reduced in order to acquire a set of pressure-volume loops to derive the end-diastolic pressure volume relation (EDPVR). From the EDPVR, the stiffness coefficient β and the operating chamber stiffness dP/dV were obtained. High frame rate echocardiographic datasets of the parasternal long axis view were acquired with an experimental ultrasound scanner (HD-PULSE) at an average frame rate of 1304±115 Hz. Tissue acceleration maps were obtained by drawing an M-mode line along the interventricular septum in order to visualize shear waves after MVC (at end-diastole). The propagation speed was assessed by semi-automatically measuring the slope (Figure A). Results: I/R injury led to an elevated chamber stiffness constant β (0.09±0.03 1/ml vs. 0.05±0.01 1/ml; p<0.001) and operating chamber stiffness dP/dV (1.09±0.38 mmHg/ml vs. 0.50±0.18 mmHg/ml; p<0.01). Likewise, shear wave speed after MVC increased after the induction of the I/R injury in comparison to baseline (6.1±1.2 m/s vs. 3.2±0.8 m/s; p<0.001). Shear wave speed had a moderate positive correlation with β (r=0.63; p<0.001) (Figure B) and a strong positive correlation with dP/dV (r=0.81; p<0.001) (Figure C). Conclusion: End-diastolic shear wave speed is strongly related to chamber stiffness, assessed invasively by pressure-volume loops. These results indicate that shear wave propagation speed could be used as a novel non-invasive measurement of the mechanical properties of the ventricle. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): FWO - Research Foundation Flanders